Republic Act No. 7877 as Applied: Unpacking the Legal Definition of Sexual Harassment From Decided Landmark Cases - Espino, Allen L. (Review of Women's Studies, 2023)
Republic Act No. 7877 or the Anti-Sexual Harassment Act of 1995 was passed supposedly to fill a wide policy gap in addressing a form of gender-based violence prevalent in the workplace. By defining what constitutes its violation, the law lays down the legal framework for sexual harassment in Philippine jurisdiction. Since its passage 26 years ago, the judicial system has produced a number of landmark decisions interpreting this legal definition through its application to actual cases. In light of criticisms about the insufficiency of the law itself, specifically about its failure to treat sexual harassment as sex-based discrimination, how has the Judiciary unpacked the legal definition in the exercise of its exclusive mandate to interpret the law? This article reviews several landmark cases that lay down precedence as far as mapping out what is - and what is not - sexual harassment. In totality, despite general leniency and accommodations afforded to victims of sexual harassment, the case law shows that judicial perspective regards sexual harassment as predominantly a moral wrong, rather than an act of inequality.